Creating a Sense of Place in Online Learning - Mesti Woro Mahatmi (Jurnal Komunikasi Pendidikan, 2022)
Since the increase of Covid 19 cases, the government has affirmed the implementation of online learning for all students, including university students. Online learning is a learning process conducted in a network that utilizes the internet, without face-to-faceinteractions. In practice, online learning has many obstacles which affect the success of students in the courses. Creating a sense of place in online learning can be done by improving communication between lecturers and students: humanization of students, the socialization process related to online learning, the importance of the role of lecturers in online learning, the contribution of students in online learning, learning media, guidelines and learning targets. With a conducive learning atmosphere, optimizing the role of lecturers and student contributions, can meet the desired learning targets.Efforts are made to achieve effective communication. The success of learning depends on the lecturers and students, each of which has a role that cannot be ruled out. The role of technology has a significant effect on the online learning process, such as internet access, communication media, and learning media.In the end, this effective communication effort is expected to be able to encouragestudents to play a maximum role in online learning, especially in situations where face-to-face learning is not possible, such as during a pandemic.